Exploring the industrial implementation of W–S–N coatings: a detailed study of the synthesis, compositional, structural, mechanical and multi-environment lubrication properties - Yaqub, Talha Bin (2022)
The work presents a detailed analysis of the synthesis, compositional, morphological, structural, mechanical and diverse atmosphere sliding characteristics of reactive sputtered W–S–N coatings. The aim is to perform an organized study to explore the sliding performance in three different environments (room temperature, 200 °C and dry N2) and disseminate the results to promote the application of TMD-N coatings for actual industrial implementation. All coatings are sub-stoichiometric in sulphur with respect to WS2 phase. The coatings show highly compact morphologies, as compared to the literature results. The pure WSx coating has (100) preferential orientation. However, the N-alloyed ones display strong (002) preferential orientation which is usually linked to a high sliding efficiency. The pure and W/S/N coatings exhibit a maximum hardness values of 3.7 GPa and 8.0 GPa, respectively. The minimum friction coefficient and wear rates observed for W–S–N coatings in room temperature, 200 °C and dry N2 are 0.09 vs. 7.2 × 10−8 mm3/Nm, 0.02 vs. 7.1 × 10−8 mm3/Nm and 0.03 vs. 9.3 × 10−9 mm3/Nm, respectively. On the other hand, the sliding properties at room temperature are comparable to the literature for both TMD-N and TMD-C coatings.